Los teólogos de la revolución: Clero popular y clero ilustrado (Teología, 2020)
The author points out the unique role of first magnitude that the clergy had in the first three decades of political and organizational settings in Argentina. The article presents the cultural framework of the Viceroyalty at the time of the Revolution, the centers of study of philosophy and theology in the Viceroyalty attended by secular and religious clergy and the place that religious orders had in this task. The article explains the role that the illustrated clergy -both religious and secular- had in supporting both theological and political doctrine and the foundation of the revolution. On the other hand it also studies the influence that popular clergy had in the implementation of this project. Both strata of clergy where predominantly Creole. The author choses eight theologians, all native and mostly young, five of them with a doctoral degree in theology and the remaining three with higher education in philosophy.
Keywords: Viceroyalty of the Rio de la Plata; Universities; Colegio San Carlos; Philosophy; Theology; Popular Clergy; Illustrated Clergy; May Revolution; Evangelization; Conquest